Audit of the Effectiveness of Inter-Budgetary Relations: The Case of Tourism Industry - ALIBEKOVA, Aigul; NASYROVA, Gulmira; ZHAMIYEVA, Aizhan; TOLYSBAYEVA, Madina; ALIBEKOVA, Balsheker; ZHUGUNISSOVA, Zhanargul (Journal of Environmental Management and Tourism, 2023)
At present, in the context of financial, socio-economic and political tension, in order to ensure the legal and effective conduct of the financial activities of the state, it is necessary to involve state audit, because its results precede the issuance of new laws and regulations, contribute to the effectiveness of public resource management, the adoption of competent management decisions, the right choice and setting of appropriate goals. To ensure the development of the tourism industry, comprehensive state support is needed, which includes the creation of a special system of legislative acts and the creation of favorable conditions for attracting investment and infrastructure development. Research and assessment of the public debt management system and the development of a methodology for their audit contribute to the improvement of control over the effectiveness of the formation, management and assessment of public debt. In general, the state audit for Kazakhstan is seen as a holistic and independent assessment effectiveness and activity of the audited objects, covering not only financial issues, but also all directions of their activities and with the presentation of effective recommendations based on the identified deficiencies and proposals for risk management. The article considers the organization of efficiency audit in the field of tourism, analyzes state budget expenditures in this service sector.